KEARIFAN LOKAL SUKU MANDAR “MEPUANG DAN METABE” TERHADAP PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR DI KABUPATEN POLEWALI MANDAR - Paida, Andi; Candra, Candra; Asriati, Asriati; Indrawaty, Indrawaty; Sriwahyuni, Sriwahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Indonesia is rich in diverse culture and local wisdom, one of which is the Mandar tribe tradition in Polewali Mandar Regency, West Sulawesi. This local wisdom plays an important role in forming the character of individuals and society. The "Mepuang" and "Metabe" traditions of the Mandar tribe are two examples of local wisdom that are full of moral and ethical values. Mepuang is a tradition of welcoming guests with full respect, reflecting friendliness, respect and politeness. Metabe is a tradition of mutual cooperation that emphasizes cooperation, solidarity and social responsibility. Character education aims to form students who are not only intellectually intelligent but also have noble character. The integration of local wisdom values ​​in character education in elementary schools is expected to be an effective approach in achieving this goal. This research explores how the local wisdom of the Mandar Tribe, especially the Mepuang and Metabe, can contribute to the character education of elementary school students in Polewali Mandar Regency. This research methodology uses a qualitative approach with in-depth interviews and participant observation to collect data from various sources, including teachers, students and local traditional leaders. The research results show that the integration of Mepuang and Metabe values ​​in the curriculum and school activities can form better student characters in terms of cooperation, responsibility and politeness. This research concludes that local wisdom has great potential to enrich character education in elementary schools. The implementation of local cultural values ​​not only preserves cultural heritage but also strengthens the character of the younger generation in facing the challenges of globalization. Effective integration between formal education and local wisdom is the key to the success of character education in Indonesia.